Viral hepatitis: a review of global prevalence and research progress toward elimination - Wenqi HUANG; Huiyan WEN; Jiaxin LI; Miao XU; Congling QIU; Fangfang ZENG; Dan LIU; Xujing LIANG; Xiaofeng LIANG (Zhongguo gonggong weisheng)
Viral hepatitis is one of the leading infectious diseases contributing to the global increase in mortality and posing a serious threat to global public health. In 2016, the World Health Organization (WHO) proposed the goal of eliminating the significant public health threat of viral hepatitis by 2030. This article provides a summary of the current status of viral hepatitis and relevant literature, reports on the progress made in eliminating viral hepatitis in recent years, both nationally and internationally, and describes the global prevalence of viral hepatitis. It also discusses the actions and progress made by different countries in eliminating viral hepatitis, as well as the challenges they face. The aim is to provide a reference for international and national efforts to eliminate viral hepatitis.